Einspruch gegen Übertreibungen - Michael Hüther (Wirtschaftsdienst, 2023)
In der Geldpolitik der Europäischen Zentralbank scheinen die Tauben durch Falken abgelöst worden zu sein. Dabei ist eine zu restriktive Geldpolitik eine Gefahr für die europäische Realwirtschaft und eine durch zu hohe Leitzinsen begünstigte Rezession möglichst zu vermeiden. Eine stark restriktiv ausgerichtete Geldpolitik wirkt zum jetzigen Zeitpunkt übertrieben und kann eine Geldpolitik, die zuvor bisweilen zu expansiv gewesen sein mag, ex post nicht ausgleichen. – – The monetary policy of the European Central Bank has raised questions in the recent past because of the expansive course it has maintained for too long. The policies of the ECB in recent months and announcements about the next steps also raise questions. For years, the doves in the Eurosystem had the power of interpretation and decision-making, but this now seems to lie with the hawks. After the expansive exaggerations, a restrictive phase now threatens. Such debates are reminiscent of a comparable situation 30 years ago, when the German National Bank, after reunification, embarked on a restrictive course with the same force, which irritated even committed economists, stated Olaf Sievert, longstanding chairman of the Council of Economic Experts, in 1992 in Wirtschaftsdienst.
Keywords: E52; E58; 330; Geldpolitik